2023
DOI: 10.1038/s41598-023-27576-6
|View full text |Cite
|
Sign up to set email alerts
|

Different impact on health outcomes of long-term care insurance between urban and rural older residents in China

Abstract: Long-term care insurance (LTCI) is garnering attention internationally and is being considered a public policy in a growing number of countries. Previous research has focused on the effects of LTCI in developed countries, ignoring the health outcomes of developing countries, especially in rural regions. Therefore, this study investigates whether different impact on health outcomes is present in the effects of LTCI between urban and rural residents in China. We employed a quasi-experimental design with data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Scholars such as Xueqin Deng and Jin Feng have assessed the policy effects in a pilot city [ 20 , 21 ], and found that LTCI can effectively reduce the burden on families and healthcare. Some of the studies used publicly available databases to assess the effectiveness of LTCI, but did not accurately correspond to the provisions for the disabled population in each pilot city [ 22 ], or did not include the non-covered population in the pilot city in the control group [ 23 ]. Therefore, this paper focuses on the effect of LTCI on healthcare utilzation among disabled middle-aged and elderly people, selects appropriate data and methods for accurate analysis and substantive discussion, and explores the heterogeneity of LTCI’s policy effects across regions and different disabled populations from a health equity perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars such as Xueqin Deng and Jin Feng have assessed the policy effects in a pilot city [ 20 , 21 ], and found that LTCI can effectively reduce the burden on families and healthcare. Some of the studies used publicly available databases to assess the effectiveness of LTCI, but did not accurately correspond to the provisions for the disabled population in each pilot city [ 22 ], or did not include the non-covered population in the pilot city in the control group [ 23 ]. Therefore, this paper focuses on the effect of LTCI on healthcare utilzation among disabled middle-aged and elderly people, selects appropriate data and methods for accurate analysis and substantive discussion, and explores the heterogeneity of LTCI’s policy effects across regions and different disabled populations from a health equity perspective.…”
Section: Introductionmentioning
confidence: 99%